Hialuronska kislina - naravna učinkovina za vlaženje in zaviranje znakov staranja kože - Kravos, Klara (Farmacevtski vestnik, 2015)
Hyaluronic acid, also known as hyaluronan, is a naturally occurring molecule, that is physiologically present in the entire body, including the skin. It is a polymeric molecule, which is increasingly used in skin-care cosmetic products and pharmaceutical care products as an active ingredient. Hyaluronic acid has many different roles in skin care products, the article is focused on its moisturizing effect and slowing down or camouflaging the signs of aging.
Keywords: hialuronska kislina; vlaženje; koža; izdelki za zaviranje staranja; kozmetični izdelki